PENGARUH LAMA PENGASAPAN MENGGUNAKAN KAYU KOSAMBI (Schleichera oleosa) TERHADAP SIFAT FISIK DAN AKSEPTABILITAS SE’I DAGING BABI (The Effect of Smoking Duration Using Kosambi Wood (Schleichera oleosa) on the Physical Properties and Acceptability of Se’i Pork) - Yan Buntu; Sauland Sinaga; Kusmajadi Suradi (Jurnal Ilmu dan Teknologi Peternakan, 2020)
Se’i is a traditional processed pork product in East Nusa Timor which is made through the smoking process using smoke of Kosambi wood so that the meat is more durable and has a distinctive taste. The objective of the research was to determine the best smoking duration on the physical properties and acceptability of pork. The research was conducted experimentally according to a Completely Randomized Design with three treatments of smoke duration and six replications. The experiments cosisted of 60(P1), 70(P2) and 80(P3) minutes, respectively. Physical properties parameters (water holding capacity, tenderness, and smoking loss) were analysed by analysis of varians, while acceptability parameters (color, taste, and flavor) were determine using Kruskal Wallis test. Polynomial orthogonal test was performed to determine the trends of the effect of treatments on the measured variables. The results of the research showed that duration of smoke curing on pork significantly affect the physical properties especially on the tenderness and smoking loss parameters, but did not influence the water holding capacity of pork. Furthermore, the increasing length of smoking application was followed by the decreasing of water holding capacity value (Y = 41,92-0.250X;  R2 = 0,99), while in contrast, positive trend was observed on the smoking loss variable (Y = 18,98 + 0,226X; R2 = 0,94). On the other hand, tenderness follows the Quadratic pattern as Y = 0.084x2 - 11.97x + 495.0 R² = 1). A majority of panelists in this study also favored of Se’i meat which was smoked by kosambi wood for 60 minutes compared to a longer duration. Therefore, smoking duration for 60 minutes is the best treatment to obtain better physical properties of pork as well as a higher level of acceptance.